Assessing experiential augmentation of the environment in the valuation of wine: Evidence from an economic experiment in Mt. Etna, Italy. Issue 6 (1st March 2019) - Pappalardo, Gioacchino; Selvaggi, Roberta; Pecorino, Biagio; Lee, Ji Yong; Nayga, Rodolfo M.
Abstract: In this study, we conducted an experimental auction to determine the impacts that "experiential augmentation, " a phenomenon in which a physical location impacts decision‐making, has on consumers' willingness to pay (WTP) for wine. The experiment elicited subjects' valuation under experiential augmentation conditions for three types of wine grown in the Mt. Etna area in Sicily, Italy. Our findings indicate that experiential augmentation increased consumers' WTP for wine. Our results suggest that experiential marketing practices explicitly related to the environment where the wine is produced and consumed can lead to increased valuation for wine.